Pelindungan Hukum Terhadap Konten Kreator Anak - Perdana, Rizki Gusti; Wardani, Susilo (Ajudikasi : Jurnal Ilmu Hukum, 2023)
Content creators are flexible workers who are in demand by all groups, both adults and children. Children in digital content creation are at risk of exploitation and psychological distress. This is the case with Monella Sunshine Jo, a 5 year old celebrity who has achieved a significant level of popularity. Although children's rights in the digital world have been regulated in legislation, adequate regulations to protect children as content creators are still lacking, creating problems that need attention. This article aims to analyze the legal regulation of child labor as a content creator on social media and the legal protection of child content creators based on labor law. The method used in this research is normative research method, which examines and analyzes the subject matter with the substance of the Legislation. Based on the results of this study it can be concluded, First, legal protection of child content creators on social media and regulations in Indonesia have regulated the rights and obligations of children as workers, especially in the entertainment industry, but there are certain conditions, stating that children who have worked must do work in accordance with their requests and talents, these provisions are regulated in the Decree of the Minister of Manpower Number KEP.115/MEN/VII/2004. Second, the protection of children from work is regulated in Law Number 13 of 2003 concerning Manpower with the exception of children aged 13-15 years who may do light work as long as it does not interfere with development and health. Conditions such as written permission, work agreement, maximum time of 3 hours, daytime, and not interfering with school. Law Number 13 of 2003 on Labor prohibits child labor that endangers health, safety, or morals, as well as involving children in slavery, prostitution, the production of pornography, and the trafficking of addictive substances.